Chemical composition of leaves and stems of BRM sorghum genotypes of mutant and normal - Aguilar, Poliana Batista de; Assis Pires, Daniel Ananias de; Santos Rodrigues, Jose Avelino; Moncao, Flavio Pinto [UNESP]; Reis, Sidnei Tavares dos; Junqueira de Sales, Eleuza Clarete; Tolentino, Daniela Cangussu (Univ Fed Grande Dourados, 2015)
Twenty genotypes of Sorghum bicolor cv. Bicolor x Sorghum bicolor cv. Sudanense as to the nutritional value: content of dry matter, cellulose, hemicellulose, lignin, neutral detergent insoluble nitrogen and acid detergent insoluble nitrogen in leaves, stems and whole plant. The experimental design was randomized blocks and comparison of means was performed by the Scott-Knott test at 5 % probability. No difference (p>0.05) between genotypes in relation to dry matter, cellulose, hemicellulose, and NIDA NDIN of leaves and of stems was observed. There was no difference (p>0.05) between the genotypes regarding lignin sheet, however in relation to lignin culm was no difference (p<0.05) among genotypes. The mean levels ranged from 4.41 to 8.63 % for the CMSXS205AxTX2785bmr and IS10428xTX2784 respectively. The isogenic mutant genotype CMSXS156AxTX2785bmr underperformed compared to its normal value pair. The experimental genotypes of sorghum mutants and normal BRM present similar chemical composition, however the presence of the gene bmr-6 mutant genotypes reduces the lignin from the stalks.
Keywords: forage; isogenic; mutation; brown midrib